Organizational Commitment, Competence, Motivation, and Work Culture on Job Satisfaction and Performance of the Kampar Police BHABINKAMTIBMAS - Andi Wardana; Rizaldi Putra; Harry Patuan Panjaitan (Journal of Applied Business and Technology, 2022)
The purpose of this study was to determine the effect of organizational commitment, competence, motivation, and work culture on job satisfaction and performance of Bhabinkantibmas Polres employees in Kampar Regency. The method used in collecting data in this study was a questionnaire. The population in this study were all employees of the Bhabinkantibmas Polres Kampar totaling 120 members of the Bhabinkantibmas. While the sample of this study was 120 respondents where using the census method. The data analysis technique in this study uses descriptive analysis and Equation Model Structure analysis (SEM) with the help of SmartPLS 3.0 software. The results showed that organizational commitment and competence were significantly positive on job satisfaction. Motivation is significantly positive on Job Satisfaction. Work culture is not significant to job satisfaction, organizational commitment is not significant to employee performance. Competence is significantly negative on employee performance. Motivation is not significant to employee performance. Work culture and job satisfaction are not significant to employee performance at Bhabinkantibmas Polres in Kampar Regency.